The epidermal growth factor receptors as biological targets in penile cancer. (April 2015) - Di Lorenzo, Giuseppe; Buonerba, Carlo; Ferro, Matteo; Calderoni, Giuseppe; Bozza, Giovanni; Federico, Piera; Tedesco, Beatrice; Ruggieri, Vitalba; Aieta, Michele
<x xml:space="preserve">Abstract</x> Penile cancer is a rare disease, with an incidence that is higher in less developed countries and is in the range of 1 – 10 per 100000 men worldwide. Early diagnosis is essential for cure, as 5 year cancer-specific survival is 90 – 100 % in patients with intraepithelial neoplasms and in those with low-grade superficial tumors without lymphovascular invasion, but it drops to 30% in men with multiple mobile or bilateral inguinal lymph nodes. The EGFR family plays a major role in penile cancer biology, with distinct receptors being involved in HPV-positive and -negative tumors. A number of anti-EGFR agents were used in penile cancer patients outside the context of a clinical trial, mainly as a salvage treatment after failure of first-line chemotherapy. A total of 28 patients received anti-EGFR monoclonal antibodies, with 50% of them showing a response to treatment, and a median PFS of ∼ 3 months. The rarity of the disease poses great challenge in terms of education and awareness of the general population, planning of preventive measures on a large scale, as well as conduction of prospective trials and approval of high-cost biological therapy.